تاریخی شہر مکہ کے ادارہ جاتی نظم کے خدو خال اور قصی بن کلاب کی مساعیCharacteristics of the Institutional System of the Historic City of Mecca and the efforts of Qusai Ibn Kilāb (Al-Qamar, 2021)
Due to the extraordinary importance of Mecca in Islam and the world history, discovery of the traces of its ancient civilization is of paramount importance. The significance of this kind of investigation is doubled when the qualities of a leader, belonging to the ancestors of the Prophet of Islam are being highlighted. Qusai Ibn Kilāb, one of the ancestors of the Prophet, was a person whose character must be understood in the context of cultural history of Mecca. In this perspective, the present paper explores the institutional system of the historic city of Mecca and the efforts of Qusai Ibn Kilāb in this regard. The study discovers that, in those days, the chief of the tribe called sheikh was looked upon with great respect. He never used his authority against his tribe, nor did he fall prey to any conspiracy that would bring disrepute to his tribe. Sheikh Qusai Ibn Kilāb, after assuming the leadership in Mecca, rendered valuable services to the people of the city. His efforts had far-reaching effects, the biggest result of which was love and affection and a sense of sacrifice for each other. The fragmented power of the tribes was consolidated. If such activities are started in a society and every status bearer participates in them, the dream of prosperity and development of the relevant society can be very much fulfilled. From Qusai's golden role, the study deduces that every dignitary and noble person in the society should play a full role in restructuring and welfare of his nation
Keywords: Mecca; history; institutions; role; Qusai Ibn Kilāb